Restorative Justice in the Case Verdict of the Muhammed Bin Zayed: MBZ Toll Road Case - Alwi, Mohammad; Mandala, Subianta; Herman, KMS (Jurnal Global Ilmiah, 2024)
Traffic congestion is a common problem throughout the country. Traffic accident cases that occur in the West Java Regional Police are generally handled through criminal procedures rather than non-criminal. The purpose of this study is to analyze and understand the implementation of the concept of Restorative Justice in cases of traffic accident decisions and other legal products in solving cases. The method used is empirical juridical using primary legal data, secondary legal data and tertiary legal data, namely legal products relevant to the restoration of justice. The results of the study explained the issuance of Law No. 22 of 2009 concerning Road Traffic and Transportation and the Circular Letter of the Chief of Police of the Republic of Indonesia. Police Number: SE/8/VII/2018 concerning the Implementation of Justice and Criminal Justice Decisions to resolve traffic accident cases. The persons involved as well as the legal requirements regarding the time limit for the implementation of justice only react to criminal investigations before submitting the initial notice of investigation, and the principle of civil law culture through the process of implementing the concept of Restorative Justice.